Pengaruh Perubahan Guna Lahan Terhadap Infiltrasi Di Hulu Das Beringin - Sukmawardhono, Nova Ambar; Nugroho, Prihadi (Universitas Diponegoro, Indonesia, 2020)
Land-use change affects the hydrological cycle of any watershed, as occurred in the upper Beringin Watershed in Mijen District and Ngaliyan District, Semarang. These areas have experienced land use change with an increasing population density, facilities, and infrastructure. Consequently, many vacant and open lands have turned to built-up areas. The purpose of this study is to determine the level of significance of the land-use change effect on water infiltration. Â The data used are satellite images and rainfall that occurred in 2010, 2014 and 2018. The study applies quantitative spatial analysis methods to measure land-use change and hydrological analysis to measure the level of infiltration thickness. The results are analyzed by using SPSS software to determine the level of significance of its influence. The results show that the land-use change has occurred in a linear path. Settlement areas have increased by 2.07% while the plantation areas decreased by 2.24%. An increase in industrial areas by 1.82% contradicts to a decrease in paddy fields by 1.45%. Also, an increase in open spaces by 4.09% corresponds to the decline in the grassland areas by 4.30%.The infiltration thickness shows that the CN value had increased from 83.33 in 2010 to 85.57 in 2018. The land-use change in the upper Beringin Watershed has no significant effect on the infiltration thickness with a value of RÂ² = 65.9%